A representação de infância nas obras de Lourenço Filho (1932-1956) - Rocha, Angélica Pinho Martins (2019)
This target of this work is the investigate of the representation of childhood in the works of Lourenço Filho from 1932 to 1956. The period delimited is justified by the publication of the Pioneers Manifest of the New School in the year 1932 and the publication of the last volume of the Graduated Series of Reading Pedrinho of Melhoramentos (Edition), in 1956. The hypothesis was raised that in the selected works will be identified different conceptions of childhood, once the Escolanovistas exalt the specificity of the child in each biological and psychological stage of the development. However, this hypothesis was deconstructed in ascertaining that there was the construction of a bourgeois, one and universal childhood, that is, the initial assumption was resolved throughout this study. In an effort to study children, interdisciplinarity was taken into account in order to dialogue with the different areas of knowledge. In the midst of this dialogue, it was possible to see that there is no child of biology, sociology, pedagogy, but there are different children, without associating them in the educational aspect only. There are different childhoods, as a human group, located in the multiple geographic territories in different chronologies, the literature was a useful source for this finding, not being used in the interdisciplinary course, only. The work of Colin Heywood (2004) was inspiring to take another look at the representation of childhood, this work influenced the reflection of the introductory assumption of this thesis, for the definition of analytical categories, we guide in the work of Elias (1994) when defining the following categories: social behavior of the being, intergenerational relations and influence of the social and geographic context to be configured in this study. The main object of study is childhood in its multiple representations or only representation, the importance of this study, is on the path to visualize childhood with a micro power, able to influence other groups, their peers and be agents of their own story. However, if for a long time this perspective was omitted, or neglected, to visualize childhood, we will use the microscope to delineate a clear and comprehensive representation of childhood in the works of Lourenço Filho from 1932 to 1956. Remember that Lourenço Filho and the Escolanovista movement are "background cloths" for this plot, and their selected works are sources, to discuss the bounded problematic.